Peer Support System and School Climate Management: A Strategic Approach to Building an Anti-Bullying Culture - Muh. Amar; Andi Kasmawati; Mustaring Mustaring; Najamuddin Najamuddin; Bakhtiar Bakhtiar; Fitriani. K (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study examines the strategic role of peer support systems and school climate management in fostering an anti-bullying culture in secondary schools in Jeneponto, Indonesia. Using a qualitative case study approach, data were collected through interviews, observations, and document analysis involving teachers, principals, and students. The findings reveal that bullying is deeply rooted in patriarchal social structures and reinforced by weak school climate management. Peer support Systems function as informal yet effective emotional networks that promote empathy and Solidarity among students. However, the absence of institutionalized mechanisms limits Their sustainability. The study suggests Integrating peer-based interventions with Inclusive school climate management to establish a participatory, equitable, and gender-responsive education system.